2014
DOI: 10.1095/biolreprod.113.114249
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of MMP1, MMP3, and MMP9 in the Chicken Ovary in Response to Gonadotropins, Sex Hormones, and TGFB11

Abstract: Matrix metalloproteinases (MMPs) are a specific class of proteolytic enzymes that play critical roles in follicular development and luteinization in mammals. However, the role of MMPs in avian ovary remains largely unknown. We found that three MMP genes (MMP1, MMP3, and MMP9) were significantly up-regulated in 23-wk-old (laying phase) chicken ovaries compared with 6-wk-old ovaries (prepubertal phase). In reproductively active chicken ovary, MMP1 expression (both mRNA and protein) remained low in prehierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 66 publications
3
40
0
Order By: Relevance
“…Previously, MMP9 has been shown to be expressed in porcine GCs (Basini et al 2011). In chicken ovary, MMP9 mRNA levels in GCs were discovered significantly higher than in theca cells and its protein expression was found in both the conditioned medium and the GC lysate, showing GCs could be considered as important cellular origin of MMP9 protein (Zhu et al 2014). Here our data was consistent with the study by Costello et al (2009), who found that the expression of MMP9 was decreased in SMAD4 mutant embryonic stem cells and embryoid bodies, indicating that SMAD4 functional loss led to decrease the expression of MMP9.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, MMP9 has been shown to be expressed in porcine GCs (Basini et al 2011). In chicken ovary, MMP9 mRNA levels in GCs were discovered significantly higher than in theca cells and its protein expression was found in both the conditioned medium and the GC lysate, showing GCs could be considered as important cellular origin of MMP9 protein (Zhu et al 2014). Here our data was consistent with the study by Costello et al (2009), who found that the expression of MMP9 was decreased in SMAD4 mutant embryonic stem cells and embryoid bodies, indicating that SMAD4 functional loss led to decrease the expression of MMP9.…”
Section: Discussionmentioning
confidence: 95%
“…The amplification curves and melting curves of each PCR product were checked to verify the amplification efficiencies and the targeted amplicon. The CT value of each gene was normalized against the average CT of GAPDH (housekeeping gene) to generate delta CT (ΔCT; Zhu et al., ). Target gene expression levels were determined by the comparative threshold cycle (ΔCT) method (Schmittgen & Livak, ).…”
Section: Methodsmentioning
confidence: 99%
“…The MMP family belongs to zinc‐ and calcium‐dependent metalloproteinases and encompasses at least 28 members that can be subdivided into four broad classes: collagenases, gelatinases, stromelysins, and membrane‐type MMPs . Several members of the MMP family (e.g., MMP1, MMP2, MMP7, MMP9, and MMP13) are expressed in mammalian ovarian follicles at different developmental stages, and the expression of these MMPs is highly regulated in response to gonadotropins, sex hormones, and growth factors . For instance, MMP1 and MMP9 are expressed in granulosa cells at all follicular stages, and MMP2 is expressed in the granulosa/cumulus cells of early and antral follicles .…”
Section: Introductionmentioning
confidence: 99%